(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
In this article, we explore the effectiveness of incorporating play into the learning process to enhance student engagement, foster creativity, and develop critical thinking skills. By examining the benefits of play-based learning, practical strategies, and real-world examples, educators can harness the power of play to create dynamic learning environments that inspire curiosity and facilitate deep understanding.